New product development and at-home medical tests. Issue 2 (3rd April 2022) - Campbell, Savannah; Mitchell, Mark; Christia, Jerome; Clark, Melissa
Abstract: The COVID-19 pandemic has impacted every aspect of life and continues to affect individuals and organizations in ways no one anticipated. In an attempt to cope with alternative lifestyle patterns, many companies have formulated products and services to mitigate behavioral adjustments. Specifically, the healthcare industry has increased efforts to cope with the ramifications of this infectious disease. A focus on creating and distributing at-home testing has become a priority as companies attempt to expedite the approval, production and commercialization of tests. This paper addresses the dynamics of producing, distributing, and evaluating at-home medical tests.